2016
DOI: 10.1161/hypertensionaha.115.06194
|View full text |Cite
|
Sign up to set email alerts
|

Low-Salt Diet and Circadian Dysfunction Synergize to Induce Angiotensin II–Dependent Hypertension in Mice

Abstract: Blood pressure exhibits a robust circadian rhythm in health. In hypertension, sleep apnea, and even shift work, this balanced rhythm is perturbed via elevations in nighttime blood pressure, inflicting silent damage to the vasculature and body organs. Herein, we examined the influence of circadian dysfunction during experimental hypertension in mice. Using radiotelemetry to measure ambulatory blood pressure and activity, the effects of angiotensin II administration were studied in wild-type (WT) and Period isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Other animal models of non-dipping hypertension have been identified using chronic models (Ivy et al, 2016) or ablation of multiple genes (Pati et al, 2016) (Masuki et al, 2005). In depth testing of Period isoform KOs in 129/sv mice by Rudic and colleagues further supports the importance of the PER proteins in blood pressure regulation (Pati et al, 2016). In this study, Angiotensin II infusion into Per2 KO mice in total darkness for 3 weeks elicited a non-dipping phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other animal models of non-dipping hypertension have been identified using chronic models (Ivy et al, 2016) or ablation of multiple genes (Pati et al, 2016) (Masuki et al, 2005). In depth testing of Period isoform KOs in 129/sv mice by Rudic and colleagues further supports the importance of the PER proteins in blood pressure regulation (Pati et al, 2016). In this study, Angiotensin II infusion into Per2 KO mice in total darkness for 3 weeks elicited a non-dipping phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Cry1/Cry2 global KO mice exhibit salt-sensitive hypertension (Saifur Rohman et al, 2005), (Doi et al, 2010). Mice lacking all three Period isoforms lose their BP dip on a low salt diet (Pati et al, 2016). Thus, the clock is a major regulator of baseline BP and rhythmic BP.…”
Section: Introductionmentioning
confidence: 99%
“…Per1 knockout mice also display a hypotensive phenotype while maintaining diurnal BP variation. Per2 and Per triple knockout (knockout of Per1 , Per2 , and Per3 ), however, do not show any difference in BP under normal conditions compared to controls [85]. Cry -null mice appear to have a unique BP phenotype in that they display a normal blood pressure and rhythm, but develop salt-sensitive hypertension when placed on a high salt diet [86].…”
Section: Integration Of Circadian Control Throughout the Nephronmentioning
confidence: 99%
“…Further, the molecular clock also appears to regulate a variety of BP control mechanisms such as aldosterone, but the nature of this complex relationship is far from evident. It is also worth noting that the zeitgeber for blood pressure rhythm does not appear to be light or the central clock since BP rhythms are maintained in total darkness [85]. …”
Section: Integration Of Circadian Control Throughout the Nephronmentioning
confidence: 99%
“…11 In the current issue of Hypertension , Rudic’s laboratory report on studies that may provide further insight into the relationship between angiotensin-II (Ang-II) and circadian dysfunction. 12 They used mice deficient in one or more isoforms of the Period genes, and found that circadian dysfunction, Ang-II, and low salt may synergize to cause non-dipping hypertension via alterations in the RAS pathway.…”
mentioning
confidence: 99%